2016
DOI: 10.1111/ddi.12483
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of habitat change and protected areas on alpha and beta diversity of Mexican birds

Abstract: Aims To investigate how habitat change and different levels of protection interact to determine variation in the (alpha and beta) diversity of bird communities in three bioclimatic zones, considering the impacts of non-native species, and the contribution of these effects to global (gamma) diversity.Location Sierra Gorda Biosphere Reserve, central Mexico.Methods We carried out bird surveys in a number of locations which varied according to their underlying vegetation type, their level of protection and the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
2
15
0
5
Order By: Relevance
“…Our results corroborate studies in temperate regions that found that protected areas do not protect all species and thus do not always affect species richness 6,36 . However, they contrast with what was known in the tropical regions based on two previous global-scale studies of protected area effectiveness, based on the meta-analysis of local-scale studies contrasting protected versus unprotected sites.…”
Section: Assessing Effectiveness In Tropical Forest Hotspotssupporting
confidence: 91%
“…Our results corroborate studies in temperate regions that found that protected areas do not protect all species and thus do not always affect species richness 6,36 . However, they contrast with what was known in the tropical regions based on two previous global-scale studies of protected area effectiveness, based on the meta-analysis of local-scale studies contrasting protected versus unprotected sites.…”
Section: Assessing Effectiveness In Tropical Forest Hotspotssupporting
confidence: 91%
“…We cannot conclude that the colonization of novel plant habitats by unique taxa will increase overall regional diversity (e.g. Hiley, Bradbury, & Thomas, ; Sax & Gaines, ; Vellend et al, ), but our results imply that a mixture of longer standing and more novel plant habitats may retain diversity, albeit with a changed composition.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, areas with low human-induced disturbance can have higher species richness than a pristine area, as predicted by the intermediate disturbance hypothes is (Roxburgh et al, 2004). Accordingly, Hiley et al, (2016) found lower alpha avian diversity in Mexican PAs than in unprotected areas. However, our results contrast with previous studies investigating this question such as Coetzee et al (2014) or Gray et al (2016), who found a positive effect of PAs on species richness and on summed abundance, including in North America (Coetzee et al, 2014).…”
Section: Discussionmentioning
confidence: 81%